EFEKTIVITAS PELAKSANAAN PROGRAM GERAKAN LITERASI SEKOLAH MELALUI READING CHALLENGE DI SMA PLUS AL-GHIFARI BANDUNG - Yuyun Siti Khoeriyah; Rosiana Nurwa Indah; Rifqi Zaeni Achmad Syam (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2021)
This study aims to describe the effectiveness of the implementation of the School Literacy Movement program through the Reading Challenge by using general effectiveness theory according to Campbell JP (1989) which consists of program success, target success, program satisfaction, input and output levels, and goal achievement. thorough. In this study, the approach used by researchers is a qualitative approach. Data collection techniques are collected through interviews and literature studies. The results of this study show that the implementation of the School Literacy Movement (GLS) program at Al-Ghifari Plus High School is sufficient to achieve program success with the participation of students. In this program, although in general, not all students take part in this activity because it is not required, the obstacles faced in implementing the Reading Challenge program at Al-Ghifari High School are students having difficulties in describing it in a fishbone diagram because of the large number of school subject assignments.